Prediksi Peluang Perpindahan Merek Handphone Menggunakan Rantai Markov Di RW 03 Air Tawar Barat Padang - Mamad Hardiyanto; Yerizon Yerizon; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2021)
Abstract –Variety mobile phone brand on the market,gives a great probability on consumers to make mobile phone brand switching from one brand to another brand. Thus giving a challenge to the mobile phone companies to seek measures should be made to obtain or retain consumers. The purpose of this research was to know Markov chain model on the mobile phone brand switching in RW 03 Air Tawar Barat Padang and the probability handphone brand switching in the future.This type of research is applied research using Markov chain analysis. Based on the research results, obtained from the Markov chain models displacement mobile phone as seen in matrix P and consumer probability switching on several mobile phone brands in the future is the brand “Others” (23.68%), Nokia (21.05%), Samsung (17.21%), Blackberry (13.35%), iPhone (10.13%), Oppo (7.74%), and brand Advan (6.85%). Keywords – Markov Chain, Probability mobile phone brand switching.Abstract –Variety mobile phone brand on the market,gives a great probability on consumers to make mobile phone brand switching from one brand to another brand. Thus giving a challenge to the mobile phone companies to seek measures should be made to obtain or retain consumers. The purpose of this research was to know Markov chain model on the mobile phone brand switching in RW 03 Air Tawar Barat Padang and the probability handphone brand switching in the future.This type of research is applied research using Markov chain analysis. Based on the research results, obtained from the Markov chain models displacement mobile phone as seen in matrix P and consumer probability switching on several mobile phone brands in the future is the brand “Others” (23.68%), Nokia (21.05%), Samsung (17.21%), Blackberry (13.35%), iPhone (10.13%), Oppo (7.74%), and brand Advan (6.85%). Keywords – Markov Chain, Probability mobile phone brand switching.